2016
DOI: 10.1515/mms-2016-0040
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Pulse Measurements in Videoplethysmography

Abstract: Reliable, remote pulse rate measurement is potentially very important for medical diagnostics and screening. In this paper the Videoplethysmography was analyzed especially to verify the possible use of signals obtained for the YUV color model in order to estimate the pulse rate, to examine what is the best pulse estimation method for short video sequences and finally, to analyze how potential PPG-signals can be distinguished from other (e.g. background) signals. The presented methods were verified using data c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…In 2016, Rumiński [39] demonstrated the possibility of estimating HR from rPPG signals in the YCrCb (YUV) space using both ICA-based and PCA-based methods. The experimental results showed that the best HR estimation performance can be achieved by applying PCA to the V channel obtained from a forehead.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2016, Rumiński [39] demonstrated the possibility of estimating HR from rPPG signals in the YCrCb (YUV) space using both ICA-based and PCA-based methods. The experimental results showed that the best HR estimation performance can be achieved by applying PCA to the V channel obtained from a forehead.…”
Section: Related Workmentioning
confidence: 99%
“…In the literature, numerous names and abbreviations of this method have evolved, such as rPPG [26], camera-based PPG (cbPPG) [16], non-contact PPG (ncPPG) [46], distance PPG (DistancePPG) [34], pulse camera (PulseCam) [47], videoplethysmography (VPG) [39], imaging PPG (iPPG/ IPPG) [49], PPG imaging (PPGi/PPGI) [49], and remote imaging PPG (RIPPG) [50]. In this paper, we will use the term rPPG.…”
Section: Related Workmentioning
confidence: 99%
“…Camera-based pulse-rate measurement is an emerging topic. There are variety of abbreviations exist in the literature referring to the same or similar technology, such as remote PPG (rPPG) [6], camera-based PPG (cbPPG) [7], non-contact PPG (ncPPG) [8], imaging PPG (iPPG/IPPG) [9], PPG imaging (PPGi/PPGI) [10], remote imaging PPG (RIPPG) [11], distance PPG (DistancePPG) [12], pulse camera (PulseCam) [13], cardiovascular camera (CardioCam) [14], video PPG (vPPG) [15], video plethysmography (VPG) [16], video-based heart-rate (VHR) [17], vital signs camera (VSC) [18], etc. This may cause confusions when referring the relevant works in the literature, especially to new people entering this field.…”
Section: Rppg Systemmentioning
confidence: 99%
“…In Ref. 18 , a study on the effectiveness of YUV color space in HR measurement based on PPGI was conducted. The YUV color space consists of a luma component (Y) and two chrominance components (U: B-Y, V: R-Y), and it is used as a default for the Android OS.…”
Section: Introductionmentioning
confidence: 99%
“…Comparing the channel signals between the sRGB and the YUV color spaces, it was found that using the V channel of the YUV color space had a better performance than either using all the channels of the sRGB color space or applying ICA or PCA to all the channels of the sRGB color space. 18 In the HR measurement based on PPGI, the CIE Lab color space is also used. It is composed of a lightness component ( ) and two chromatic components ( and ), in which the Euclidean distance between two different colors is similar to the color difference perceived by the human eye.…”
Section: Introductionmentioning
confidence: 99%